Akselerasi Sertifikasi Halal di Kabupaten Sumenep Dinas Koperasi UKM, Perindustrian dan perdangangan serta UMKM Perspektif Maqashid Syari’ah - Wiamul Wafiq; Shofiyun Nahidloh; Fajar Fajar; Rio Kurniawan (Universitas 45 Surabaya, 2024)
Halal certification is a vital element in the food and consumer goods industry in Indonesia, where the majority of the population is Muslim. This certification not only serves as a guarantee that the products consumed comply with Islamic law but also acts as an instrument to enhance consumer trust and product competitiveness in the global market. Law No. 33 of 2014 on Halal Product Assurance provides a clear legal framework for the issuance of halal certificates, with BPJPH serving as the authority that issues the certificates based on halal fatwas from MUI. Sumenep Regency, located at the eastern end of Madura Island, holds significant potential in the MSME sector, particularly in the food and beverage industry. Thousands of MSME units in the region make a substantial contribution to the local economy, although many are still unable to meet the requirements for halal certification. This condition underscores the importance of synergy between the Department of Cooperatives, MSMEs, Industry, and Trade (DINKOPUKMPERINDAG) and MSMEs to accelerate the halal certification process, thereby making local products more competitive in both domestic and international markets. This study adopts a qualitative method with data collected through field surveys, in-depth interviews, and documentation conducted at DINKOPUKMPERINDAG Sumenep Regency. Primary data were obtained directly from informants in the field, while secondary data were sourced from various relevant documents and literature. The research focuses on MSMEs under the guidance of DINKOPUKMPERINDAG, aiming to understand how this synergy can accelerate halal certification from the perspective of Maqashid Sharia.